2015
DOI: 10.1007/s10067-015-2894-1
|View full text |Cite
|
Sign up to set email alerts
|

Vascular perfusion kinetics by contrast-enhanced ultrasound are related to synovial microvascularity in the joints of psoriatic arthritis

Abstract: The purpose of the study was to assess the relationship of the continuous mode contrast-enhanced harmonic ultrasound (CEUS) imaging with the histopathological and immunohistochemical (IHC) quantitative estimation of microvascular proliferation on synovial samples of patients affected by sustained psoriatic arthritis (PsA). A dedicated linear transducer was used in conjunction with a specific continuous mode contrast enhanced harmonic imaging technology with a second-generation sulfur hexafluoride-filled microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…The agents were injected with the dosage of 4.8 ml[20212223] or 2.4 ml,[24] reconstituted by a 10 ml saline solution. And, a linear transducer, ranging from 4 to 12 MHz, was required for contrast imaging.…”
Section: Methods Of Contrast-enhanced Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…The agents were injected with the dosage of 4.8 ml[20212223] or 2.4 ml,[24] reconstituted by a 10 ml saline solution. And, a linear transducer, ranging from 4 to 12 MHz, was required for contrast imaging.…”
Section: Methods Of Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…Relatively lower acoustic pressure was also selected for optimizing the detection of flow perfusion, set at about 45 kPa. [22] In recent studies, contrast-tuned imaging technology (CnTI) was emerged in evaluating the results of CEUS imaging. CnTI permitted the transmission of the frequencies of microbubbles and filtered out irrelevant signals caused by surrounding tissues.…”
Section: Methods Of Contrast-enhanced Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, low MI CEUS is superior to Doppler CEUS in detecting intra-articular microvascularity [44]. Also, the method provides valuable quantitative data through TIC, as revealed by some studies that observed positive correlations between the peak signal intensity and microvascular density (CD105+) in the case of psoriatic arthritis [45].…”
Section: Modern Clinical Applicationsmentioning
confidence: 99%
“…Indubitably, the evolution in psoriatic arthritis (PsA) knowledge represents an emblematic example [2]. Indeed, fundamental advances in understanding PsA pathogenesis and natural history have deeply changed its perception by both patients and physicians [3]. In the past, psoriasis was considered just a mere esthetic concern due to a primary defect in keratinocytes, leading to their hyper-proliferation.…”
mentioning
confidence: 99%